2019
DOI: 10.1097/iae.0000000000002679
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status and Treatment Outcomes of Vascular Endothelial Growth Factor Inhibitors for Neovascular Age-Related Macular Degeneration

Abstract: PURPOSE To assess whether smoking status affects 1-year visual outcomes in eyes treated with vascular endothelial growth factor inhibitors for neovascular age-related macular degeneration. METH-ODS Retrospective analysis of data from a prospectively designed, multicenter, observational database. Nine hundred and eighty seven treatment-naive eyes of patients with neovascular age-related macular degeneration were tracked by the Fight Retinal Blindness! outcome registry in Australia, New Zealand, Singapore, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…However, the ve-year outcomes in the CATT study reported that cigarette smoking was associated with an increased risk of poor visual prognosis (20/200 or worse) [51]. In a prospective study examining 987 eyes, nonsmokers had higher visual acuity improvements than former and current smokers [52]. In contrast, McKibbin et al demonstrated that the visual outcome associated with anti-VEGF therapy for nAMD was not signi cantly different among never smokers, former smokers, and current smokers [53].…”
Section: Discussionmentioning
confidence: 98%
“…However, the ve-year outcomes in the CATT study reported that cigarette smoking was associated with an increased risk of poor visual prognosis (20/200 or worse) [51]. In a prospective study examining 987 eyes, nonsmokers had higher visual acuity improvements than former and current smokers [52]. In contrast, McKibbin et al demonstrated that the visual outcome associated with anti-VEGF therapy for nAMD was not signi cantly different among never smokers, former smokers, and current smokers [53].…”
Section: Discussionmentioning
confidence: 98%
“…analysis that separately analysed smoking status as a potential risk factor for poor outcomes found it was associated with a lower adjusted mean (95% CI) VA change at 12 months (+4.6 [1.5, 7.8] letters) compared with ex‐smokers (+5.9 [3.4, 8.3] letters) and non‐smokers (+8.0 [6.0, 10.0] letters). 65 …”
Section: Key Findings From the Frb! Registrymentioning
confidence: 99%
“…analysis that separately analysed smoking status as a potential risk factor for poor outcomes found it was associated with a lower adjusted mean (95% CI) VA change at 12 months (+4.6 [1.5, 7.8] letters) compared with ex-smokers (+5.9 [3.4, 8.3] letters) and non-smokers (+8.0 [6.0, 10.0] letters). 65 Although macular atrophy and subretinal fibrosis are the most common causes of poor long-term outcomes for nAMD patients, adverse ocular events specifically associated with anti-VEGF therapy are quite rare. 8,66 The rarity of these events makes real-world data more suited to monitoring their rate and subsequent than RCTs.…”
Section: Poor Outcomes and Adverse Eventsmentioning
confidence: 99%
“…As AMD still is an incurable eye disease, strategies for primary and secondary prevention are of paramount importance. For example, smoking cessation can have a significant impact on the patients' prognosis and treatment response, even at an older age (Vittorio et al 2020). In addition, nonpharmacological interventions by way of nutrition and supplements have been investigated.…”
Section: Introductionmentioning
confidence: 99%